Efficacies of four plant essential oils as larvicide, pupicide and oviposition deterrent agents against dengue fever mosquito, Aedes aegypti Linn. (Diptera: Culicidae) - Aksorn Chantawee; Mayura Soonwera (Asian Pacific Journal of Tropical Biomedicine, 2018)
Objective: To evaluate larvicidal, pupicidal and oviposition deterrent activities of four plant essential oils from Alpinia galanga (L.) Willd rhizome, Anethum graveolens L. (An. graveolens) fruit, Foeniculum vulgare Mill. fruit, and Pimpinella anisum L. fruit against Aedes aegypti (Ae. aegypti). Methods: Four essential oils at 1%, 5% and 10% concentrations were assessed for insecticidal activity against larvae and pupae of Ae. aegypti, following the procedure of a dipping method assay. Oviposition deterrent activity of four essential oils was evaluated on gravid female of Ae. aegypti by a dual-choice oviposition bioassay. Results: The results revealed that An. graveolens oil provided the strongest larvicidal activity against Ae. aegypti among four tested plant essential oils with the highest mortality rate of 100% and LC50 value of -0.3%. From the pupicidal experiment, An. graveolens also showed the highest toxicity against Ae. aegypti pupae with the highest mortality rate of 100% at 72 h and LC50 value of 2.9%. In addition, 10% An. graveolens had an oviposition deterrent effect against Ae. aegypti with effective repellency of 100% and an oviposition activity index of –1.0. Conclusions: An. graveolens oil has a good potential as a larvicidal, pupicidal and oviposition deterrent agent for controlling Ae. aegypti.